2015
DOI: 10.1042/bj20141330
|View full text |Cite
|
Sign up to set email alerts
|

The motor function of Drosophila melanogaster myosin-5 is activated by calcium and cargo-binding protein dRab11

Abstract: In the Drosophila melanogaster compound eye, myosin-5 (DmM5) plays two distinct roles in response to light stimulation: transport of pigment granules to the rhabdomere base to decrease light exposure and transport of rhodopsin-bearing vesicles to the rhabdomere base to compensate for the rhodopsin loss during light exposure. However, little is known of how the motor function of DmM5 is regulated at the molecular level. In the present study, we overexpressed DmM5 in Sf9 insect cells and investigated its regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…9C ) or the presence of μM level of Ca 2+ activates the motor in vitro by destabilizing the auto-inhibited state of MyosinV. 103 However, in the cell, endogenous Rab11 is not sufficient to recruit the auto-inhibited motor to the membranes. 104 Simultaneous binding of the actin regulator Spir and Rab11 to 2 distinct sites of the GTD is necessary to trigger the recruitment of MyosinV to vesicles ( Fig.…”
Section: Integration Of Rab Activities: Control Of Complex Cellular Ementioning
confidence: 99%
“…9C ) or the presence of μM level of Ca 2+ activates the motor in vitro by destabilizing the auto-inhibited state of MyosinV. 103 However, in the cell, endogenous Rab11 is not sufficient to recruit the auto-inhibited motor to the membranes. 104 Simultaneous binding of the actin regulator Spir and Rab11 to 2 distinct sites of the GTD is necessary to trigger the recruitment of MyosinV to vesicles ( Fig.…”
Section: Integration Of Rab Activities: Control Of Complex Cellular Ementioning
confidence: 99%
“…Structural studies have revealed that myosin Vb binds both the GDP-and GTPforms of Rab11, with around 30-fold higher affinity for the GTP-form [134]. Although the binding to Rab11 has been proposed to activate the Drosophila myosin V (DmM5) [144], the mechanism of this activation and the effect on the motor properties remains to be addressed. Similarly, given the broad range of binding partners and the diverse mechanisms underlying their interaction with the myosin V isoforms, it remains unclear whether the melanophilin-induced activation and the changes in myosin Va's biophysical properties is a generally applied mechanism or not.…”
Section: Regulation By Binding Partners: Myosinmentioning
confidence: 99%
“…Double-headed class 5 myosins are evolutionary ancient, prototypic actin-based molecular motors implicated in the spatiotemporal segregation and the transport of organelles across phylogeny (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). A prerequisite for efficient transport is that a single motor can either take multiple discrete steps on an actin filament without detaching, a property also referred to as processivity, or that the motor works in an ensemble with other myosins-5 to efficiently move a cargo.…”
mentioning
confidence: 99%